Organic rice farming enhances conservation value, while water conductivity, a proxy for nutrient inputs, best predicts aquatic plant biodiversity in East-Central Europe - Gyula Pinke; János Csiky; Attila Mesterházy; László Tari; Robert W. Pal; Bálint Czúcz; Ákos Bede-Fazekas; Péter Batáry; Zoltán Botta-Dukát (Hydrobiologia, 2026)
Organic rice farming has increasingly gained attention for its potential to enhance biodiversity compared to conventional agricultural methods. In this study, we examined the abundance of plant species groups of conservation interest in rice fields in Hungary, located at the northern periphery of rice cultivation. We compared organically and conventionally managed rice fields to determine their impact on plant biodiversity. Our results indicated that organic fields generally support a greater abundance of non-harmful macrophytes, charophytes, and red-listed species. However, these differences were less pronounced in fields considered less ecologically valuable, irrespective of management types. Our analysis revealed that water conductivity had a more significant impact than farming type. Lower conductivity correlated with weed communities of higher conservation values, particularly in organically managed fields. This effect was significant compared with conventional fields but was only evident in areas with relatively low conductivity, likely reflecting low nutrient levels in the water. These findings suggest that to maximize biodiversity benefits, organic agriculture should be practiced alongside the judicious use of low amounts of organic manure or nutrients. Such practices could enhance species-rich macrophyte communities, contributing to the preservation of the unique biodiversity found in this historic rice cultivation region.

Drivers of weed species composition in Hungarian organic rice paddies - Gyula Pinke; Attila Mesterházy; János Csiky; Lászó Tari; Bálint Czúcz; Zoltán Botta-Dukát (Paddy and Water Environment, 2026)
Which factors are the most important determinants of weed species composition in organic rice fields? Which species can be associated with the extreme values of the most important background variables? To answer these questions, we surveyed the weed flora along with 15 management and 3 environmental variables in 42 organically managed rice fields in eastern Hungary. Filamentous algae, Chara vulgaris , Chara braunii , Schoenoplectus mucronatus , Elatine triandra , and Echinochloa crus-galli were the most dominant weeds. Using a minimal adequate model containing 4 terms with significant net effects, 48.3% of the total variation in weed species data could be explained. Farm holding size (correlated with sowing type, shift crop, organic manure and water depth) was found to be the most important explanatory variable, which was followed by hand weeding, tillage type (correlated with tillage depth, shift crop and supplementary nutrients) and rice cover. Farm holding size was negatively associated with most of the aquatic plants suggesting its adverse impact on farmland biodiversity. Hand weeding appeared to be efficient against Rumex stenophyllus and Echinochloa crus-galli , but it was tolerated by Cyperus difformis . Perennial weeds like Persicaria amphibia and Bolboschoenus planiculmis were more abundant in sites without soil inversion and Lemna aequinoctialis seemed to be most tolerant for the shading effect of crop canopy. The responses of weed species to the studied variables provide new information about the assembly rules of aquatic plant communities, and our findings also can be used to optimise non-chemical weed control strategies in organic rice production.

Rise and fall of Stachys annua (L.) L. in the Carpathian Basin: a historical review and prospects for its revival - Gyula Pinke; Éva Dunai; Bálint Czúcz (Genetic Resources and Crop Evolution, 2021)
Stachys annua (L.) L., a melliferous archaeophyte plant became a dominant weed of the cereal stubbles of the Carpathian Basin in the medieval three-field system. By the middle of the nineteenth century, this plant provided more than two-thirds of the Hungarian honey production, and its high quality monofloral honey turned into a characteristic brand of the Hungarian apiculture. Recognizing its importance, S. annua also briefly became a minor crop cultivated in “bee gardens” and arable fields in the late nineteenth century, possibly also in response to the first signs of its upcoming decline. Starting with the advent of the steam plough, the twentieth century has brought a drastic decline for S. annua due to a combination of deeper and earlier tillage operations, agrochemicals, and new competing weed species (in particular the common ragweed, Ambrosia artemisiifolia ). The last remnant stands of this previously dominant weed species are of considerable ecological and historical value as farmland biodiversity hotspots. These sites are important refuge for rare weeds, wild pollinators (including bumblebees), and declining farmland birds, which could be targeted by eco-schemes under the European Union’s (EU’s) greening Common Agricultural Policy. The rediscovery of the cropping potential of S. annua and the development of an appropriate technology would also allow its cultivation as a valuable bee forage, catch crop, green cover, or oilseed plant in the future.

Explaining variability in the production of seed and allergenic pollen by invasive Ambrosia artemisiifolia across Europe - Suzanne T. E. Lommen; Caspar A. Hallmann; Eelke Jongejans; Bruno Chauvel; Melinda Leitsch-Vitalos; Alla Aleksanyan; Peter Tóth; Cristina Preda; Maja Šćepanović; Huseyin Onen; Barbara Tokarska-Guzik; Paulina Anastasiu; et al. (Biological Invasions, 2018)

Relating Ambrosia artemisiifolia and other weeds to the management of Hungarian sunflower crops - Gyula Pinke; Péter Karácsony; Zoltán Botta-Dukát; Bálint Czúcz (Journal of Pest Science, 2013)

Floristic composition and conservation value of the stubble-field weed community, dominated by Stachys annua in western Hungary - Gyula Pinke; Robert Pál (Biologia, 2009)

Phytosociological and conservational study of the arable weed communities in western Hungary - Gyula Pinke; Robert Pál (Plant Biosystems, 2008)